LEGITIMATION OF SOCIAL SUBJECT SELF-IDENTIFICATION IN THE INFORMATIONAL SOCIETY - Чернієнко, В. О. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The problem of scientific interpretation of the self-identification process as person self-determination that harmonious to informational society network structures tendencies is considered in the article.